“Evaluación de trichoderma spp. Nativo y comercial a diferentes concentraciones en el control de oídio (sphaerotheca pannosa) inoculado en el cultivo de lechuga (lactuca sativa l.) Variedad batavia; en las terrazas del campus Salache - Cotopaxi, 2023.” - Santos Toapanta, Cristian Alexander (2023)
Although the availability of various biological products for the control of diseases, their use is still restricted due to the ignorance of the farmers or the mistrust of their effectiveness, therefore the present investigation was carried out on the bench terraces of the Salache campus of the Technical University of Cotopaxi. With the purpose of evaluating the effect of Trichoderma spp. Native and commercial in the control of powdery mildew inoculated in lettuce (Lactuca Sativa L.) variety batavia. The methodology of (Chacha, 2022) was used for the implementation of the crop; (Bastidas, 2012) for laboratory work on the replication of Trichoderma spp and determination of concentrations. The experimental design was the randomized complete block design (DBCA); with six treatments plus a control with three repetitions, the factors under study were Trichoderma spp. (native and comercial) and three concentrations 10^6, 10^8 and 10^10; resulting in 21 experimental units. The variables to be evaluated were incidence (%), severity (%), number of leaves (units) and harvest yield (kg). For the statistical analysis, the InfoStat software was used. The results obtained for the incidence variable show that in T6 (native Trichoderma spp. at concentration 10^10), will be present the best incidence reduction results at 10.67%; for the severity variable, the T3 treatment (commercial Trichoderma spp. at a concentration of 10^10) presented greater control with a reduction of 9.16%; for the variable number of leaves, the T3 treatment (commercial Trichoderma spp. at a concentration of 10^10), the best result was obtained with 12.67 average number of leaves per plant; finally, for the variable at harvest yield, the T3 treatment (Trichoderma commercial spp at a concentration of 10^10) obtained the best yield with 3.63 kg. Because of this the best concentration of Trichoderma spp. native and commercial was the concentration 10^10 and the most effective strain was the commercial one.